Distance Education Course about Sexuality for Obstetrics and Gynecology Residents - Vieira, Teresa Cristina Souza Barroso; Nakamura, Mary Uchiyama; Silva, Ivaldo da; Torloni, Maria Regina; Ribeiro, Meireluci Costa; Souza, Eduardo de (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Purpose To describe the experience of a distance education course on sexual issues during pregnancy and after birth for residents.Methods This prospective educational intervention study was conducted by investigators from the Universidade Federal de São Paulo, Brazil, between April and September 2014. The participants were 219 physicians (residents from the 1st to the 6th years). The duration of the course was of 24 hours (10 video lectures and online chats). At baseline, the participants answered questions about their training, attitude and experience regarding sexual issues during pregnancy and after birth; before and after the course, they answered questions to assess their knowledge about the topic; at the end of the course, they answered questions on the quality of the course. The Student t-test was used to compare the before and after scores of the knowledge tests; values of p < 0.05 were considered statistically significant.Results A total of 143 residents concluded the course; most were in their 1st (27.2%) or 3rd (29.4%) years of residency. There was a significant increase in the mean scores of the questionnaires that assessed the knowledge of the topic: 4.4 (±1.6) versus 6.0 (±1.3; maximum score: 10), before and after the course respectively (p < 0.0001). Most of the participants (74.1%) declared that the quality of the course as a whole reached their expectations, and 81.1% would recommend the course to a friend.Conclusions The online Sexology course for Obstetrics and Gynecology residents increased their knowledge about the sexual issues during pregnancy and after birth, and fulfilled the participants' expectations. The experience described here may serve as a model for other sexuality courses targeting similar audiences.
Keywords: pregnancy; sexology; medical education; resident training; distance education; obstetrics